2015
DOI: 10.1097/aud.0000000000000172
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Auditory Processing and Cognitive Abilities in Children

Abstract: A complex interaction of cognitive abilities and AP scores is evident. For many children with listening difficulties, who perform poorly on AP tasks, cognitive deficits are also in place. Although the direction of causality is unclear, it is likely that these cognitive deficits are causing the perceived difficulty and/or are having a significant effect on the test results. Interpretation of AP tests requires consideration of how cognitive abilities may have impacted on not only task results but also the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
118
3
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(142 citation statements)
references
References 65 publications
13
118
3
8
Order By: Relevance
“…In particular, this work found that the proportion of children failing to reach the 'required academic standard' increased bỹ 5% for every 2 dB increase in classroom noise level. Cognitive deficit can affect auditory processing ability [27] and it is well established that children with Type 1 diabetes are at risk of mild cognitive impairment over time [28]. The children in this study did, however, show depressed scores on the 'spatial advantage' metric, which is a difference measure derived from performance across different listening conditions.…”
Section: Discussioncontrasting
confidence: 61%
“…In particular, this work found that the proportion of children failing to reach the 'required academic standard' increased bỹ 5% for every 2 dB increase in classroom noise level. Cognitive deficit can affect auditory processing ability [27] and it is well established that children with Type 1 diabetes are at risk of mild cognitive impairment over time [28]. The children in this study did, however, show depressed scores on the 'spatial advantage' metric, which is a difference measure derived from performance across different listening conditions.…”
Section: Discussioncontrasting
confidence: 61%
“…In an investigation of links between auditory processing test results, functional deficits and cognitive abilities in a sample of 50 control and 105 children referred for auditory processing assessment, Tomlin et al (2015) found that both LE and RE FR dichotic digit test scores correlated significantly (p # 0.01) with forward and reverse digit span and nonverbal IQ, as well as with attention (p # 0.01 for LE and p # 0.05 for RE). Multiple regression analysis found that auditory working memory was a significant predictor of dichotic LE and RE performance (b 5 0.42, p , 0.001 and b 5 0.24, p , 0.01, respectively) and that nonverbal IQ was a significant predictor of FR LE performance (b 5 0.58, p , 0.01).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple regression analysis found that auditory working memory was a significant predictor of dichotic LE and RE performance (b 5 0.42, p , 0.001 and b 5 0.24, p , 0.01, respectively) and that nonverbal IQ was a significant predictor of FR LE performance (b 5 0.58, p , 0.01). Tomlin et al (2015) concluded that interpretation of auditory processing tests requires consideration of how cognitive ability may have impacted both test results and the functional difficulties experienced by the child.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a diagnostic gold standard for some of such deficits has not been established (Fortunato-Tavares et al, 2009;Marler et al, 2001), due to the individual differences among speech, language, and/or hearing-related learning disabilities. In addition, the results of recent findings suggest cognitive deficits in individuals who are suspected for these disorders (Ahmmed et al, 2014;Tomlin et al, 2015). This makes it very difficult to separate APD from the other disorders based only on behavioral tests.…”
Section: Introductionmentioning
confidence: 99%